Monsters and Marvels: Shakespeare Across Opera, Ballet, Dance, Puppetry, and Music in Central and Eastern Europe—and Beyond - Cetera-Włodarczyk, Anna; Havlíčková Kysová, Šárka; Kowalcze-Pawlik, Anna; Mišterová, Ivona; Reuss, Gabriella (Multicultural Shakespeare: Translation, Appropriation and Performance, 2023)
This collectively authored position paper discusses “hybrid” Shakespeares in Central and Eastern Europe, focusing on productions that offer formal experimentation and transnational perspectives. While their contexts remain regional, they provide an insight into how Shakspeare has been mobilised regionally. The paper consists of four distinct parts, each considering Shakespeare in a hybrid form: in opera, dance and musical theatre as well as puppetry in the transnational, regional context. The general discussions of Shakespeare’s presence/appropriation in these art forms are followed by case studies that illustrate the significance of hybridity that characterises Shakespeare in the Central and Eastern European transnational context. Our brief analyses and selected case studies suggest a need for a detailed study of Shakespeare and performative arts in Central and Eastern Europe that would concentrate on the transgressive impulse these theatrical blends realised through formal experiment and artistic innovation. The publication of the article was supported by the International Visegrad Fund, project no. 22210007, titled “Crossing Borders with Shakespeare since 1945: Central and Eastern European Roots and Routes.” The project is co-financed by the Governments of the Czechia, Hungary, Poland and Slovakia through Visegrad Grants. The mission of the Fund is to advance ideas for sustainable regional cooperation in Central Europe.